A Triple Culture Model of the Blood-Brain Barrier Using Porcine Brain Endothelial cells, Astrocytes and Pericytes - Thomsen, Louiza Bohn; Burkhart, Annette; Moos, Torben (PLOS ONE, 2015)
In vitro blood-brain barrier (BBB) models based on primary brain endothelial cells (BECs) cultured as monoculture or in co-culture with primary astrocytes and pericytes are useful for studying many properties of the BBB. The BECs retain their expression of tight junction proteins and efflux transporters leading to high trans-endothelial electric resistance (TEER) and low passive paracellular permeability. The BECs, astrocytes and pericytes are often isolated from small rodents. Larger species as cows and pigs however, reveal a higher yield, are readily available and have a closer resemblance to humans, which make them favorable high-throughput sources for cellular isolation. The aim of the present study has been to determine if the preferable combination of purely porcine cells isolated from the 6 months old domestic pigs, i.e. porcine brain endothelial cells (PBECs) in co-culture with porcine astrocytes and pericytes, would compare with PBECs co-cultured with astrocytes and pericytes isolated from newborn rats with respect to TEER value and low passive permeability. The astrocytes and pericytes were grown both as contact and non-contact co-cultures as well as in triple culture to examine their effects on the PBECs for barrier formation as revealed by TEER, passive permeability, and expression patterns of tight junction proteins, efflux transporters and the transferrin receptor. This syngenic porcine in vitro BBB model is comparable to triple cultures using PBECs, rat astrocytes and rat pericytes with respect to TEER formation, low passive permeability, and expression of hallmark proteins signifying the brain endothelium (tight junction proteins claudin 5 and occludin, the efflux transporters P-glycoprotein (PgP) and breast cancer related protein (BCRP), and the transferrin receptor).